Treatment of Pretreated Textile Wastewater Using Modified Mbbr - J.Sosamony, K; A.Soloman, P (International Journal of Engineering and Technology, 2018)
Currently, water pollution control is one of the major logical zones. The textile industry is a major pollution causing industry among the industrial pollutions. Treatment of textile effluent utilizing customary physical as well as chemical strategies is costly, produces enormous amounts of sludge and needs the expansion of lethal chemicals. BOD to COD proportion of textile effluent is low. Thus it is not appropriate to treat textile effluent by a solitary physicochemical or biological process. In this investigation, the textile effluent is dealt with utilizing Moving Bed Bio-film Reactor (MBBR) with the magnetic field after improving the biodegradability by the solar photo-Fenton process. The carriers in MBBR is inoculated with azoarcus bacteria isolated from textile sludge. The fundamental  parameters as pH, carrier filling ratio and contact time were optimized utilizing Box Behnken factual design. The MBBR process has most extreme efficiency at pH 7, filling ratio of 62% and a contact time 2.4 days. In this optimum condition 68.9% BOD and 80% COD  are expelled. At the point when the pretreated wastewater was dealt with MBBR reactor under the influence of magnetic field, the efficiency of the treatment is additionally expanded, so 87.4% COD expulsion and 87% BOD evacuation were accomplished at 12 mT attractive field power when exposure time was at 12 hrs.